2013
DOI: 10.2176/nmc.53.323
|View full text |Cite
|
Sign up to set email alerts
|

Acute Subdural Hematoma Requiring Surgery in the Subacute or Chronic Stage

Abstract: The aim of this study was to clarify the clinical characteristics and pathophysiology of conservatively treated cases of acute subdural hematoma (ASDH) that ultimately require surgery in the subacute or chronic stage, and devise an appropriate form of management for them. A total of 50 patients with ASDH were admitted to our institution during a 5-year period. Hematoma removal in the subacute or chronic stage was performed in 8 patients. The ASDH had been caused by a fall in 5 patients. Five patients had been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 6 publications
0
35
0
1
Order By: Relevance
“…2,3,9,11,14 In a few previous reports bur hole surgery was performed for subacute SDH, with good outcomes. 5,6,16 Yamada et al reported on 20 patients in whom subacute SDH was treated with bur hole surgery. 16 Eighteen patients underwent surgery once, with no recurrence, and good recovery was achieved in 77.8% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,9,11,14 In a few previous reports bur hole surgery was performed for subacute SDH, with good outcomes. 5,6,16 Yamada et al reported on 20 patients in whom subacute SDH was treated with bur hole surgery. 16 Eighteen patients underwent surgery once, with no recurrence, and good recovery was achieved in 77.8% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…A hematoma formed between the dura mater and arachnoid is called a subdural hematoma (SDH), and it is known to occur in 5% to 29% of all head trauma patients 1619). It can even occur in patients with no trauma or minor trauma, such as those who take anticoagulants, have a blood disease, or have received a hydrocephalus shunt 7141519).…”
Section: Introductionmentioning
confidence: 99%
“…A subacute SDH (SASDH) is a hematoma occurring between 4 and 20 days after injury 69). Surgical treatment is required if neurological symptoms progress from mild to moderate or severe due to injury during the subacute stage (e.g., decreased consciousness, motor nerve palsy, headache), while patients receive conservative treatment for mild neurological symptoms due to acute SDH 6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Common causes of mandible fracture include physical assault, sports activities, motor vehicle accidents, industrial accidents, warfare, and falls. 3 Factors affecting fracture include the direction and amount of force as well as the biomechanical and anatomical properties of bone.…”
mentioning
confidence: 99%